POSSIBILITIES FOR DEVELOPMENT OF COMMODITY EXCHANGE IN SERBIA - Jankovic, Irena; Jelocnik, Marko; Zubovic, Jovan (Economics of Agriculture, 2018)
The aim of the paper is the analysis of the current situation related to the spot and non-standardised term commodity exchange market, as well as to provide a proposal for further improvement of commodity-trading in Serbia. The system of commodity-exchange trading in Serbia has not been developed and legislation has not been fully enacted. According to the analysis of price variability on three commodity markets it can be concluded that the fluctuations of prices of agricultural products in the last decade were very high, which led to market participants need for term commodity exchange instruments. The paper presents suggestions for further improvement of the spot market as well as the clearing model on the forward market. The adoption of the Law on Commodity Exchange and amendments to the Law on Capital Market would improve the spot trading, trading of non-standardised and standardised term contracts.